Relaxant Action of Diclofenac Sodium on Mouse Airway Smooth Muscle - Chen, Chunfa; Yang, Yongle; Yu, Meng-Fei; Shi, Shunbo; Han, Shuhui; Liu, Qing-hua; Cai, Congli; Shen, Jinhua (Frontiers in Pharmacology, 2019)
Diclofenac sodium (DCF) is a nonsteroidal anti-inflammatory drug (NSAID) and is widely used as an analgesic and anti-inflammatory agent. Herein, we found that DCF could relax high K+ (80 mM K+)-/ACh-precontracted tracheal rings (TRs) in mice. This study aimed to elucidate the underlying mechanisms of DCF-induced relaxations. The effects of DCF on airway smooth muscle (ASM) cells were explored using multiple biophysiological techniques, such as isometric tension measurement and patch-clamping experiments. Both high K+- and ACh-evoked contraction of TRs in mice were relaxed by DCF in a dose-dependent manner. The results of isometric tension and patch-clamping experiments demonstrated that DCF-induced relaxation in ASM cells was mediated by cytosolic free Ca2+, which was decreased via inhibition of voltage-dependent L-type Ca2+ channels (VDLCCs), nonselective cation channels (NSCCs), and Na+/Ca2+ exchange. Meanwhile, DCF also enhanced large conductance Ca2+ activated K+ (BK) channels, which led to the relaxation of ASMs. Our data demonstrated that DCF relaxed ASMs by decreasing the intracellular Ca2+ concentration via inhibition of Ca2+ influx and Na+/Ca2+ exchange. Meanwhile, the enhanced BK channels also played a role in DCF-induced relaxation in ASMs. These results suggest that DCF is a potential candidate for antibronchospasmic drugs used in treating respiratory diseases such as asthma and chronic obstructive pulmonary disease.